The role of microRNAs involved in the disorder of blood–brain barrier in the pathogenesis of multiple sclerosis - Emami Nejad, Asieh; Mostafavi Zadeh, Seyed Mostafa; Nickho, Hamid; Sadoogh Abbasian, Ali; Forouzan, Azim; Ahmadlou, Mojtaba; Nedaeinia, Reza; Shaverdi, Saham; Manian, Mostafa (Frontiers in Immunology, 2023)
miRNAs are involvedplay a role in various vital processes,includingsuch as cell growth, development, apoptosis, cellular differentiationandpathological cellular activities.CirculatingmiRNAs can be detected in various body fluids including serum, plasma, saliva, and urine.It is worth mentioning that miRNAs remain stable in the circulation in biological fluids and are released from membrane-bound vesicles called exosomes, which protect them from RNase activity.It has been shown that miRNAs regulate blood-brain barrier integrity by targeting both tight junction and adherens junction molecules and also can influence the expression ofon inflammatory cytokines. Some recent studies have examined the impact of certain commonly used drugs in Multiple Sclerosis on miRNAslevels. In this review, we will focus on the recent findings on the role of miRNAs in multiple sclerosis, including their role in the cause of MS and molecular mechanisms of the disease, utilizing miRNAs as diagnostic andclinical biomarkers, using miRNAs as a therapeutic options modalityor targets for Multiple Sclerosis and drug responses in patients, and their importance as prognosticators of disease progression highlighting their potential as a future treatment goal for MS.